PENGARUH TERAPI RELAKSASI GENGGAM JARI UNTUK MENURUNKAN NYERI PADA KASUS POST SECTIO CAESAREA - Dini Kurniawati; Handayani Woro Ganjaran; Nadirzyah Hafiz Arif; Turatno Turatno; Wahyuningsih Wahyuningsih (SINERGI : Jurnal Riset Ilmiah, 2026)
Sectio Caesarea (SC) is an alternative birth process, especially for those who have difficulty giving birth normally, but nowadays CS has become an option for mothers who give birth so that the incidence of SC is increasing. This surgical procedure causes changes in the continuity of body tissue. In the surgical process, anesthesia is used so that the patient does not feel pain, but after the operation is completed the patient begins to be aware and feels pain in the part of the body that has been operated on. Pain that occurs after surgery is a pressing or stressful event, and can change the lifestyle and psychological well-being of an individual. Common complementary therapies for patients with pain problems are meditation, autogenic training, relaxation training, guided imagery, rhythmic breathing, operant conditioning, biofeedback, building a therapeutic relationship, therapeutic touch, skin stimulation, hypnosis, music, acupressure, and aromatherapy. Based on the background above, we carry out nursing care to apply the results of research regarding nursing care for patients with post-SC pain by providing finger-holding relaxation therapy.